2018
DOI: 10.3389/fchem.2018.00197
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Assisted Esterification of Valeric Acid to Alkyl Valerates Promoted by Biosilicified Lipases

Abstract: A novel, environmentally friendly, and sustainable ultrasound-assisted methodology in the valorization of valeric acid to alkyl valerate using a biosilicified lipase from Candida antarctica is reported. This one-pot room temperature methodology of enzyme biosilicification leads to biosilicified lipases with improved activity and reaction efficiency as compared to free enzymes. Yields in the ultrasound-promoted esterification of valeric acid was ca. 90% in 2 h with 15% m/v of biosilicified lipase (Bio-lipase; 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Despite these protein losses, the biocatalyst still retained significant amounts of lipase, remaining highly active during the investigated esterification reactions. These relevant results further supported the high stability of the immobilised enzymes compared with the free enzyme, particularly under the investigated conditions [ 20 ].…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…Despite these protein losses, the biocatalyst still retained significant amounts of lipase, remaining highly active during the investigated esterification reactions. These relevant results further supported the high stability of the immobilised enzymes compared with the free enzyme, particularly under the investigated conditions [ 20 ].…”
Section: Resultssupporting
confidence: 53%
“…The hydrolytic free and immobilized enzyme, Candida antarctica lipase B (CalB), was employed in order to study the efficiency of the encapsulation or biosilicification procedure, conducted by CH and MW methodologies. The immobilized lipase was previously characterized by our group using different techniques such as Brunauer-Emmett-Teller surface area analysis (BET), thermogravimetric analysis (TGA) and X-Ray Photoelectron Spectroscopy (XPS) [ 20 ]. The reported results indicated that the biocatalyst started being a non-porous material, becoming highly porous after successive reuses due to the progressive loss of organic compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent novel approach based on lipase encapsulation by using biomimetic silica mineralization (the so-called biosilicification) was proved to offer the possibility to render active and stable biocatalysts entrapped within a silica support. A lot of experiments are executed with Candida Antarctica lipase. One example shows that gel-entrapped CRL lipase was prepared by polycondensation of hydrolyzed tetramethoxysilane and isobutyltrimethoxysilane but certain modifications were introduced into the conventional immobilization procedure.…”
Section: Current and Promising (Industrial) Applicationsmentioning
confidence: 99%
“…To overcome the previously mentioned problems, heterogeneous catalysts were designed and employed in esterification reactions for the production of biofuels, including sulfonic resins [7], zeolites [8], and others based on zirconium oxide [9] and niobic acid [10]. Alternatively, this esterification reaction can be performed enzymatically under mild conditions [11,12].…”
Section: Introductionmentioning
confidence: 99%